2019
DOI: 10.4018/978-1-5225-7519-1.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Earthquake Data

Abstract: Seismology, which is a sub-branch of geophysics, is one of the fields in which data mining methods can be effectively applied. In this chapter, employing data mining techniques on multivariate seismic data, decomposition of non-spatial variable is done. Then k-means clustering, density-based spatial clustering of applications with noise (DBSCAN), and hierarchical tree clustering algorithms are applied on decomposed data, and then pattern analysis is conducted using spatial data on the resulted clusters. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The most popular is the K − M ean algorithm, which is based on the shortest distance between the data and the centroid ( [7]). In some specific cases this algorithm has been applied for the spatial clustering of earthquakes ( [8], [9]) however, recently, it is often considered as benchmark for assessing the performance of more advanced clustering techniques ( [10], [11], [12]). The main drawback of the k-means algorithm is that the optimal number of clusters is not automatically determined and different techniques could be considered for selecting this parameter ( [13]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular is the K − M ean algorithm, which is based on the shortest distance between the data and the centroid ( [7]). In some specific cases this algorithm has been applied for the spatial clustering of earthquakes ( [8], [9]) however, recently, it is often considered as benchmark for assessing the performance of more advanced clustering techniques ( [10], [11], [12]). The main drawback of the k-means algorithm is that the optimal number of clusters is not automatically determined and different techniques could be considered for selecting this parameter ( [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [11] compared the results of K-means and DBSCAN, for clustering seismic events, showing the better performance of the DBSCAN algorithm. Savaş et al [12] described three principal techniques for clustering seismic events: the k-Means, DBSCAN and hierarchical tree clustering algorithms. By applying them to the spatial seismic events of the USGS they concluded that the results are compatible with the reality.…”
Section: Introductionmentioning
confidence: 99%